Greenland, Gregory Valley, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1933)
Figure 218. Looking east down Gregory Valley from Gregory Glacier (in foreground). (XIII) 45-25 [1933]. Gregory Valley.